Face-Threatening Acts and Mitigation Strategies in the Context of Physical Discomfort: A Pragmatic Analysis of the YouTube Talk Show Hot Ones - Devika Fatimah Azzakhro; Irman Nurhapitudin; Andang Saehu (English Language in Focus (ELIF), 2026)
Face management plays an important role in interview interaction, especially when speakers need to maintain their public image in challenging situations. Previous studies have examined Face-Threatening Acts (FTAs) and politeness strategies in different interview settings. However, little attention has been paid to how FTAs and mitigation strategies develop as speakers experience increasing physical discomfort. The YouTube talk show Hot Ones provides a unique setting in which guests answer interview questions while eating increasingly spicy food. This study examines the types of FTAs and the mitigation strategies used by the host and guests in three Hot Ones episodes featuring Ariana Grande, MrBeast, and Jennie. Using qualitative discourse analysis based on Brown and Levinson's politeness theory, the study analysed 37 FTAs. The findings show that positive-face threats were much more common (33 cases) than negative-face threats (4 cases). Positive politeness was the most frequently used mitigation strategy, followed by off-record, negative politeness, and bald-on-record. Although all bald-on-record strategies occurred during the final stage of the challenge, positive politeness remained the dominant strategy throughout the interviews. The findings also show that physical discomfort forms part of the interactional context in which speakers negotiate face, but it does not determine their pragmatic choices. This study extends research on face management by showing how embodied experience and digitally mediated interaction shape face negotiation in entertainment interviews.